2018
DOI: 10.1002/jbmr.3391
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pre-ESRD Serum Calcium With Post-ESRD Mortality Among Incident ESRD Patients: A Cohort Study

Abstract: Albumin-corrected serum calcium (cSCa) decline at late stages of chronic kidney disease and rise after dialysis initiation. Although hypercalcemia is associated with higher mortality in end-stage renal disease (ESRD), there are scarce data on the impact of pre-ESRD cSCa on post-ESRD mortality. Therefore, we used a large national cohort of 21,826 US veterans who transitioned to dialysis in all US Department of Veterans Affairs health care facilities over 2009 to 2014 to examine the associations with all-cause a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…Prior studies reported the association between higher corrected calcium and poor prognosis 8,9 . This association might be partly explained by overestimation of calcium status among patients with hypoalbuminemia, who are at high risk for mortality 26 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Prior studies reported the association between higher corrected calcium and poor prognosis 8,9 . This association might be partly explained by overestimation of calcium status among patients with hypoalbuminemia, who are at high risk for mortality 26 .…”
Section: Discussionmentioning
confidence: 97%
“…The reason for this discrepancy might reside in the www.nature.com/scientificreports www.nature.com/scientificreports/ different timings of blood sampling; calcium levels were measured just before the first dialysis in this study, while they were measured during the first 91 days of dialysis in the previous study. Corrected calcium levels increased after dialysis initiation among patients with low corrected calcium levels 8 , likely because of a positive calcium balance during dialysis 20 , active vitamin D treatment, and/or calcium-based phosphate binders. Despite the discrepancy, approximately 60% of the patients with true hypocalcemia were incorrectly categorized as normocalcemia using corrected calcium both in our cohort and in the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Transition of Care in CKD study cohort has been previously described (11)(12)(13)(14)(15)(16). Briefly, a retrospective cohort study was performed examining United States veterans with incident ESKD who transitioned to kidney replacement therapy from October 1, 2007 to March 30, 2014.…”
Section: Study Populationmentioning
confidence: 99%
“…The analytical cohort was derived from the United States Renal Data System (USRDS) Special Study Center Transition of Care in CKD, which aimed to investigate incident ESRD US veterans who transitioned to ESRD between October 1, 2007 and March 30, 2014 [18-23]. Of the original population of 85,505 veterans derived from USRDS records, we excluded patients without data on follow-up ( n = 1,958) and with missing date of birth ( n = 3).…”
Section: Methodsmentioning
confidence: 99%